Game analysis of merchants and consumers confronting fakes on e-commerce platforms. Issue 1 (1st January 2021) - Guo, Hongfeng; Zhao, Xinyao; Yu, Hang; Zhang, Xin; Li, Jinjin
Abstract : With the rapid development of e-commerce, selling fake commodities happens more frequently. It is closely related to consumers' interests, merchants' online word of mouth, and e-commerce platforms' long-term development. To explore and analyse this problem, an evolutionary game model is constructed among a merchant, an e-commerce platform, and a consumer. Some factors are considered in the model, such as online word of mouth of the merchant and punishment mechanism of the platform. Then stable strategies are obtained for all participants and the influence of each factor on the choices of their strategies is analysed. The stability of equilibrium points is discussed through the Jacobian matrix and Lyapunov's indirect method. And evolutionary stable strategy combinations are obtained. The results show that e-commerce platforms' supervision and consumers' evaluations are shown to have important impacts on merchants' behaviours; reducing supervision costs and increasing punishment on merchants can help improve the enthusiasm of platforms' supervision clearly; and merchants' negative online word of mouth brings about potential economic losses. At last, the influence of each factor on the evolution of each participant's strategies is simulated by Matlab 2014a. And potential evolutionary stable strategy combinations of the game system are verified under different conditions.